2020
DOI: 10.1111/tmi.13354
|View full text |Cite
|
Sign up to set email alerts
|

Stability of extemporaneous sulfadiazine oral suspensions from commercially available tablets for treatment of congenital toxoplasmosis

Abstract: Objectives To determine the physicochemical and microbiological stability of sulfadiazine suspensions (100 mg/mL) in simple syrup (A) and sorbitol (B) formulations prepared from commercially available tablets. Methods An ultra‐performance liquid chromatographic assay was developed and validated to determine the chemical stability of sulfadiazine. Three samples were prepared and stored at 5 and 25 °C and assayed at 0, 7, 14 and 30 days. Physical parameters (appearance, pH, particle size and viscosity) were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…The preparations were produced at a concentration of 100 mg/mL (Costa et al, 2020;Ferreira et al, 2016) to achieve the therapeutic dosage with the smallest volume of the formulation, considering the dosage for the treatment of congenital toxoplasmosis is 100 mg/ kg/day divided into two administrations. Additionally, formulations with smaller volumes are usually better tolerated by children (Khan et al, 2022;Nakama et al, 2019;Reis et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The preparations were produced at a concentration of 100 mg/mL (Costa et al, 2020;Ferreira et al, 2016) to achieve the therapeutic dosage with the smallest volume of the formulation, considering the dosage for the treatment of congenital toxoplasmosis is 100 mg/ kg/day divided into two administrations. Additionally, formulations with smaller volumes are usually better tolerated by children (Khan et al, 2022;Nakama et al, 2019;Reis et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To opt i m i ze t he prev iou sly developed chromatographic technique (Costa et al, 2020), a UPLC method was validated using a gradient elution to provide separation of SDZ and methylparaben. With the optimization, the SDZ peak was detected at 2.6 minutes, and methylparaben was detectable at 7.3 minutes only when concentrated solutions were analyzed (data not shown), which is due to the difference in concentration between SDZ and methylparaben (Supplementary information; Figure S1).…”
Section: Uplc Methods Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Drugs are compounded as suspensions in order to meet the needs of special patients such as pediatric, geriatric and tube-fed patients (Cutaia et al, 2018;Allen, 2019). Studies have reported variations in pH, viscosity, particle size distribution, API content and microbial contamination of extemporaneous preparations, and suggested that such preparations were suitable for use only for a specified period of time, thus leading to the introduction of beyond-use-dates (BUD), after which the preparation cannot be consumed (Alfred-Ugbenbo et al, 2017;Silva et al, 2020;Soares Rodrigues Costa et al, 2020). However, the bioavailability and palatability of such preparations can still not be proven, even though they have been found to be physically, chemically or microbiologically stable, until they are supported by evidenced based data (Belayneh and Tessema, 2021).…”
Section: Introductionmentioning
confidence: 99%